Analysis of Service Science Design through Customer Experience to Increase PosAja Application User Satisfaction - Sukma Rukmana; Wiwik Handayani (Kontigensi : Jurnal Ilmiah Manajemen, 2023)
The PosAja mobile application is a digital service owned by Pos Indonesia in the field of delivery. Despite being downloaded by more than 100K users, the PosAja application has experienced a decline in rating and application productivity. This research intends to represent user complaints through review data analysis and develop a more effective and efficient service science design based on user experience. The research method applied is descriptive quantitative with data analysis applying SVM to classify positive and negative sentiments from review data. Model evaluation was carried out by training the training and test data subsets 3 times with variations of k = 5, k = 7, and k = 10. The results showed that the best accuracy was obtained with an accuracy of 89.98% on the SVM_kernel Sigmoid parameter. Analysis of review data revealed that the sentiment of PosAja application users tends to be negative compared to positive sentiment on the Google Play Store. To improve user experience and satisfaction, service science design development should focus on continuous improvement and evaluation of the PosAja application.